Meningkatkan Empati Siswa Melalui Bimbingan Kelompok dengan Teknik Brainstorming - Dini, Rahmah; Tanjung, Romi Fajar (Program Studi Bimbingan dan Konseling FKIP UMSU, 2025)
This study aims to determine the effect of group guidance with brainstorming techniques in increasing student empathy. The background of this study is the importance of developing empathy as part of students' emotional intelligence in the school environment. The research method used is quantitative method with experimental research type with One Group Pretest-Posttest design. The research sample was 10 students who were determined using cluster sampling. The data in this study were obtained through pretest and posttest, then analyzed using descriptive statistics, normality test, and hypothesis testing with paired sample t-test method. The results of the analysis showed a significant increase in the level of student empathy, where the average empathy score rose from 88.10 in the pretest to 100.70 in the posttest. The significance value of 0.001 (0.05) in the hypothesis test shows that group guidance with brainstorming techniques has a significant effect on increasing student empathy. Thus, it can be concluded that this service is not only effective in increasing empathy, but also able to create a refreshing atmosphere and encourage students' active involvement in the guidance process.